Dashboard Business Intelligence Vusialisasi Data Akreditasi Sekolah Pada SMP Negeri 1 Sembawa - Amru Setio Wibowo; Andri Andri (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
This study aims to create a business intelligence dashboard to support school accreditation at SMP Negeri 1 Sembawa in the form of data visualization. In this study, several business intelligence dashboards were produced with the aim of providing convenience for schools in supporting the school accreditation process. Business intelligence is a tool to manage data and perform data analysis that can support school accreditation which will be collected into a data mart and the analysis process is carried out in the form of a cube. For the ETL process using the help of SQL Server Management Studio and SQL Server Development software and as a design for the dashboard creation using the Power BI software. This research has several dashboards including student achievement dashboard based on achievement level, student achievement dashboard based on year of achievement, and student achievement based on graduation which can be seen by year and gender of students.